Enhancing Elementary Students’ Computational Thinking through 'Code4Kids' Coding-Based Worksheets - Rafni Fajriati; Martines Martines; Rizki Julia Utama (Heca Sentra Analitika, 2026)
This study investigates the early-stage development and feasibility of the Code4Kids worksheet, an unplugged coding-based instructional resource designed to enhance computational thinking (CT) and digital literacy among fourth-grade elementary students. An exploratory Research and Development (R&D) approach was employed, focusing on needs analysis, prototype development, and expert validation. Data were collected through classroom observations, teacher interviews, and structured expert evaluations to examine contextual readiness, instructional design alignment, and pedagogical suitability. The needs analysis revealed limited student digital literacy, insufficient structured CT materials, and low teacher confidence in implementing coding-related instruction. Based on these findings, a theory-informed worksheet prototype integrating decomposition, pattern recognition, abstraction, and algorithmic thinking was developed. Expert validation results (mean score = 4.6/5) and positive teacher feedback indicate that the prototype is developmentally appropriate, pedagogically coherent, and feasible for classroom implementation in low-resource settings. The study concludes that unplugged, worksheet-based coding materials can serve as an accessible entry point for integrating CT in elementary education. These findings provide an empirical foundation for future classroom trials and broader implementation of the Code4Kids model.